KEBIJAKAN AMERIKA SERIKAT KELUAR DARI JOINT COMPREHENSIVE PLAN OF ACTION (JCPOA) - Fadhila Ulfa; Ahmad Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research is based on the decision of Donald Trump as the 45th President of the United States on May 8, 2018 which announced that the United States officially ended the Joint Comprehensive Plan of Action (JCPOA). JCPOA is a nuclear agreement formed by Iran with the P5 + 1 countries of the United States, Britain, France, Russia, China plus the European Union which is represented by Germany. these countries are permanent members of the UN Security Council. This research uses the Behavioralism Perspective. This perspective discusses political analysis based on the study of individual political behavior. This research uses foreign policy theory and idiosyncratic theory. Idiosyncratic is an internal resource that influences policy. The level of analysis in this study is individuals. The focus of research is at the level of individual analysis in humans as the main character.This research method is explanatory that explains the existence of a causal relationship about why an event occurs. United States decision to end the JCPOA is caused by the influence of Donald Trump's leadership personality which can be analyzed from idiosyncratic factors such as temperament, social context, cognition and motives. these aspects shape the personality of a leader and ultimately have an impact on how leaders make decisions. Keyword: Foreign Policy, JCPOA, United States, Iran, Donald Trump, Idiosyncratic